Calculation of deception probability of netted radar based on non-central chi-square distribution - Yue Yuan; Gang-yi Tu; Ben Wang; Ling-ling Wang (International Journal of Distributed Sensor Networks)
Aiming at the problems of complex factors affecting the rate of deception probability of networked of radar nets, the large amount of calculation by Monte Carlo simulation and the inability to quantitatively analyze the influence of various factors on the deception probability of networked, a calculation method of deception probability of networked is proposed. First, according to the homology measurement method based on the Mahalanobis distance, the probability density model of the deception probability of networked is calculated. Its probability density model obeys the non-central chi-square distribution. Then, a hypothesis test model is established to calculate the deception probability of networked mathematical expression. The simulation results show that the error between the calculation method of the deception probability of networked and the calculation result of 1000 times Monte Carlo is less than 2%. The method in this article can analyze the quantitative effect of false target position, interference distance interval, radar position, true target position, and other factors on the deception probability of networked, instead of Monte Carlo simulation, to provide a trade-off between the true target recognition rate and the deception probability of networked theoretical basis.